Does preventive regulation reduce stock price synchronicity? Evidence from Chinese annual report comment letters - Xiaomin Hao (Elsevier, 2021)
Based on a sample of Chinese A-share listed firms from 2015 to 2018, this paper studies the impact of annual report comment letters (ARCLs) on firm stock price synchronicity. We find that after firms receive ARCLs, their stock price synchronicity decreases. Moreover, the longer the ARCLs and the more negative the ARCLs’ tone, the lower the resulting stock price synchronicity. The mechanism test shows that after firms receive ARCLs, the firms’ information disclosure increases in quantity and quality, external media attention increases, and the firms’ governance improves, reducing their stock price synchronicity. Further research shows that this negative association is more significant in firms with higher information asymmetry. This paper shows that the ARCL, an innovative application of the capital market supervision philosophy, is conducive to improving the quality of listed firms and to the healthy development of the capital market.